Efecto de un biodegradador enzimático comercial en la producción de biol a partir de jacinto de agua (eichhornia crassipes solms) - Mendieta Morrillo, Edward Edgardo (2019)
This research was carried out at the Escuela Superior Politécnica Agropecuaria de Manabí, Manuel Félix López with the aim of generating an alternative of use of the water hyacinth (Eichhornia crassipes Solms) existing in the reservoir "Sixto Durán Ballén" (La Esperanza), taking as factors in study the doses of the commercial enzyme degrader and water proportion more biomass in the elaboration of Biol. A completely randomized block design (DBCA) was used with 5 replications, and Tukey's mean comparison test was used at 0.05% of error probability, presenting significant differences in all treatments. It is concluded that the dose of the gradient against the proportion of water hyacinth more biomass is not significant, however it was identified that the greater quantity of biomass is the volume obtained from Biol, giving as better treatments to T3 (35cc of BYZ-96 + 50% of Water + 50% biomass), T6 (50cc BYZ-96 + 25% water + 75% biomass), and T9 (65cc BYZ-96 + 25% water + 75% biomass).